The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2020
DOI: 10.3389/fmed.2020.00361
|View full text |Cite
|
Sign up to set email alerts
|

Advances in the Involvement of Gut Microbiota in Pathophysiology of NAFLD

Abstract: Non-alcoholic fatty liver disease (NAFLD) is characterized by hepatic steatosis and progresses to non-steatohepatitis (NASH) when the liver displays overt inflammatory damage. Increasing evidence has implicated critical roles for dysbiosis and microbiota-host interactions in NAFLD pathophysiology. In particular, microbiota alter intestine absorption of nutrients and intestine permeability, whose dysregulation enhances the delivery of nutrients, endotoxin, and microbiota metabolites to the liver and exacerbates… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
38
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 54 publications
(44 citation statements)
references
References 186 publications
(205 reference statements)
0
38
0
Order By: Relevance
“…It is also important to highlight the importance of Kupffer cell activation and lymphocyte recruitment, because apart from the effects mentioned before, leukocyte presence in the liver tissue is a classic histopathological sign of metabolic steatohepatitis. 72 Increasing evidence suggests that the gut-liver axis can take part in the onset of hepatocellular carcinoma, particularly due to the dysbiosis-induced endotoxemia. For example, gut microbial metabolites that act as antigens, like lipoteichoic acids in the case of Gram-positive bacteria or LPS in Gram-negative bacteria, can induce synthesis of the prostaglandin E2 PGE2 by hepatic stellate cells, which reduces the antitumoral activity of CD8+ lymphocytes.…”
Section: Gastrointestinal Microbiome In Obesity T2dm Mafld and Alcomentioning
confidence: 99%
See 1 more Smart Citation
“…It is also important to highlight the importance of Kupffer cell activation and lymphocyte recruitment, because apart from the effects mentioned before, leukocyte presence in the liver tissue is a classic histopathological sign of metabolic steatohepatitis. 72 Increasing evidence suggests that the gut-liver axis can take part in the onset of hepatocellular carcinoma, particularly due to the dysbiosis-induced endotoxemia. For example, gut microbial metabolites that act as antigens, like lipoteichoic acids in the case of Gram-positive bacteria or LPS in Gram-negative bacteria, can induce synthesis of the prostaglandin E2 PGE2 by hepatic stellate cells, which reduces the antitumoral activity of CD8+ lymphocytes.…”
Section: Gastrointestinal Microbiome In Obesity T2dm Mafld and Alcomentioning
confidence: 99%
“…The mechanisms behind these protective effects are the reduction of hepatic lipid accumulation, less endotoxemia, oxidative stress and activation of anti-inflammatory pathways through the modulation of NF-κB and TNF production, as well as the regulation of collagen production. 72,75,76 For example, a study conducted by Xin et al 75 showed prevention of the onset of hepatic steatosis and cellular apoptosis in mice fed with a high-fat diet through the administration of the probiotic Lactobacillus johnsonii BS15; the end result was an improvement in hepatic inflammation and oxidative stress. A more recent study by Liang et al 77 gave a compound of probiotics to a group of mice fed with a high-fat diet and Fig.…”
Section: Treatment Of Mafld With Probioticsmentioning
confidence: 99%
“…Indeed, bariatric surgery can increase circulating levels of glucagon-like peptide-1 (GLP-1), which, in turn, decreases appetite, slows gastric emptying, and improves insulin sensitivity [ 47 ]. In addition, GLP-1 modulates bile acid signaling via the farnesoid X receptor (FXR), which can alter the gut microbiome and promote NAFLD [ 48 , 49 ]. With these premises, current guidelines indicate that bariatric surgery can be a potential option in patients with T2DM or in those with severe obesity (i.e., BMI >35 kg/m 2 ) [ 1 , 2 ].…”
Section: Introductionmentioning
confidence: 99%
“…The liver plays an important role in metabolism and interacts with all tissues and organs ( 31 ). Histological examination showed that compared with the LFD group, HFD increased liver fat accumulation ( Supplementary data and Figures S2A, B ), but the treatment of exercise and/or leucine had not shown effects on elimination of adiposity in the liver ( Supplementary Data and Figures S2A, B ), which was consistent with the results of tissue weight.…”
Section: Resultsmentioning
confidence: 99%